Repair of ultraviolet light-induced damage in Micrococcus radiophilus, an extremely resistant microorganism. - Lavin, M F (1976)
Repair of ultraviolet radiation damage was examined in an extremely radioresistant organism, Micrococcus radiophilus. Measurement of the number of thymine-containing dimers formed as a function of ultraviolet dose suggests that the ability of this organism to withstand high doses of ultraviolet radiation (20,000 ergs/mm2) is not related to protective screening by pigments. M. radiophilus carries out a rapid excision of thymine dimers at doses of ultraviolet light up to 10,000 ergs/mm2. Synthesis of deoxyribonucleic acid is reduced after irradiation, but after removal of photodamage the rate approaches that in unirradiated cells. A comparison is drawn with Micrococcus luteus and M. radiodurans. We conclude that the extremely high resistance to ultraviolet irradiation in M. radiophilus is at least partly due to the presence of an efficient excision repair system.